2003
DOI: 10.1046/j.1523-1755.2003.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Classification and rescue of ROMK mutations underlying hyperprostaglandin E syndrome/antenatal Bartter syndrome

Abstract: In contrast to previous reports, most of the investigated ROMK mutations displayed a trafficking defect that might be rescued by pharmacologic agents acting as molecular chaperones. The evaluation of different disease-causing mechanisms will be essential for establishing new and more specific therapeutic strategies for HPS/aBS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 38 publications
(72 reference statements)
6
53
0
4
Order By: Relevance
“…When examined under steady-state conditions in mammalian cells, ROMK primarily resides in the ER (35,41). Similarly, we found that the majority of ROMK1S44D+K80M co-migrated with the ER-resident protein Sec61 when lysates from a wild-type yeast strain isogenic to trk1Δtrk2Δ and its derivatives (BY4742) were subjected to subcellular fractionation by sucrose gradient sedimentation analysis ( Figure 1D).…”
Section: Identification Of a Romk Variant Suitable Formentioning
confidence: 91%
See 1 more Smart Citation
“…When examined under steady-state conditions in mammalian cells, ROMK primarily resides in the ER (35,41). Similarly, we found that the majority of ROMK1S44D+K80M co-migrated with the ER-resident protein Sec61 when lysates from a wild-type yeast strain isogenic to trk1Δtrk2Δ and its derivatives (BY4742) were subjected to subcellular fractionation by sucrose gradient sedimentation analysis ( Figure 1D).…”
Section: Identification Of a Romk Variant Suitable Formentioning
confidence: 91%
“…Interestingly, individuals heterozygous for a type II Bartter mutant allele exhibit resistance to hypertension, most likely because of decreased NKCC2-mediated reabsorption of sodium (40). Of the >50 identified Bartter syndrome-associated mutations in ROMK, many appear to affect ROMK trafficking or post translational modification when ectopically expressed in Xenopus laevis oocytes (41). To date, therapies for Bartter syndrome are not curative and patients require lifelong multi-drug treatments and potassium supplementation.…”
mentioning
confidence: 99%
“…AQP2 mutations that are responsible for autosomal recessive NDI are characterized by misrouting of the misfolded mutant proteins and are trapped in the endoplasmic reticulum (53). Mutants that encode other renal membrane proteins that are responsible for Gitelman syndrome (54), Bartter syndrome (55,56), and cystinuria (57) are also retained in the endoplasmic reticulum.…”
Section: X-linked Ndi (Omim 304800) As a Results Of Mutations In Avpr2mentioning
confidence: 99%
“…Mutation of any of these six residues alters the pH i sensitivity of Kir1.1 (645). R311W and A177T, which are found to cause Bartter's syndrome, change pK a of Kir1.1 (ϳ6.5) to 9.2 and 7.8 in Kir1.1, respectively, which results in dysfunction of the channel in physiological pH i range (617,645,696) (see also sect. VA6 and Table 2).…”
Section: Pore Structure and Functionmentioning
confidence: 99%